2009
DOI: 10.1097/qai.0b013e3181b62933
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Baseline CD4 Cell Counts on the Clinical Significance of Short-Term Immunologic Response to Antiretroviral Therapy in Individuals With Virologic Suppression

Abstract: Background Achieving virologic suppression is a clear therapeutic goal for patients receiving combination antiretroviral therapy (cART). However, the effects of immunologic responses, whether measured as CD4 count changes from baseline or CD4 counts at follow-up, in patients with virologic suppression, have not been clearly established. Methods Treatment-naive individuals aged ≥16 years, who initiated cART between 1998 and 2005 in participating cohorts of the ART Cohort Collaboration and achieved viral load … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…In contrast, after 24 weeks of treatment, d4T-treated patients had a significantly higher Hb level than that seen in the AZT arm, and had a larger CD4 count increase than that observed in both the AZT and TDF arms. These changes could be pertinent in settings where patients start ART with low CD4 counts, since the magnitude of CD4 count rise following treatment is associated with improved clinical outcomes in patients with low nadir CD4 counts [13]. Our findings may have important implications for treatment programs in resource-limited settings where patients generally start treatment late and anemia is frequent.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, after 24 weeks of treatment, d4T-treated patients had a significantly higher Hb level than that seen in the AZT arm, and had a larger CD4 count increase than that observed in both the AZT and TDF arms. These changes could be pertinent in settings where patients start ART with low CD4 counts, since the magnitude of CD4 count rise following treatment is associated with improved clinical outcomes in patients with low nadir CD4 counts [13]. Our findings may have important implications for treatment programs in resource-limited settings where patients generally start treatment late and anemia is frequent.…”
Section: Discussionmentioning
confidence: 91%
“…We further subdivided the cohort by extent of CD4+ T-cell count change over time, using a change cutoff of at least +/− 50 cells/μL (Binquet et al 2001; Moore et al 2009; Palella et al 2003); the three categorical CD4 change groups are characterized in Table 2. The categorical CD4 change analysis confirmed the findings: there was a significant overall effect for abnormal white matter and subcortical gray matter volumes in the full regression models.…”
Section: Resultsmentioning
confidence: 99%
“…Change in current CD4 was assessed both as a continuous variable, calculated as the difference in square root transformed CD4 count between the two visits, and as a categorical one. The categorical approach used a change cutoff of at least +/− 50 cells/μL, reflecting numerous published reports showing this degree of CD4 change to be associated with important clinical events (Binquet et al 2001; Moore et al 2009; Palella et al 2003). Categories of CD4 change included: Increasing, Decreasing, and Minimal change (less than 50 cells) groups which are characterized in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…+ T cell count responses are likely to be better defined in terms of absolute post-cART CD4 + T cell counts, rather than change from baseline, 12 and would explain why most of the studies have not shown meaningful clinical outcome differences between NNRTI and PI regimens.…”
Section: Discussionmentioning
confidence: 99%
“…11 Second, there are data suggesting that clinically important CD4 + T cell count responses are likely to be better defined in terms of absolute postcART CD4 + T cell counts rather than change from baseline. 12 Finally, the effect of different regimens on parameters involved in immune function and their relationship with different gains of CD4 + have not been assessed in a randomized clinical trial. Moreover, most previous studies addressing the effect of cART on immune restoration have analyzed only a few of the multiple parameters altered in HIV infection.…”
Section: Introductionmentioning
confidence: 99%